Evaluation of an NGO supported agroforestry program : the Nepal Agroforestry Foundation (NAF) program in Kunwari village of Ramechhap district of Nepal - Pandit, Bishnu Hari; Upasena, S.H.; Weber, Karl E.; Boonjit Titapiwatanakun; Nepal Agroforestry Foundation (Bangkok : Asian Institute of Technology, 1994)
The survey finding is based on the field studies conducted during Dec. 15, 1993 - March 10, 1994 in two villages namely Kunwari and Gaikhura of Ramechhap District of Nepal to assess the impact of the Nepal Agroforestry Foundation (NAF) support program. The program is being implemented by Tamakosi Sewa Samiti (TSS). The major finding of the study reveals that the fodder trees promotion program of NAF has played a significant role in the increase of the level of income of farmers in project village (Kunwari). The regression model explains that 84 percent variation in the total farm income is due to fodder tree adoption by the farmers. The study shows that only 23.3 percent of the farming households are under subsistence level in project village. This shows a quite satisfactory result when compared to national average (49%). An adult literacy program of TSS is associated with the level of fodder tree adoption by farmers. Similarly, fodder tree is also associated with the size of land and animal holdings. These components have positive relationship with each other. The species, Marus alba, is highly preferred by farmers among eight fodder tree species tested in a pair-ranking test based on criteria like growth, palatability and fodder in dry season. Premna latifolia and Leucaena species have significant relationship with milk production in buffalo. The analysis of cropping patterns shows that lowlands are more intensively used than uplands and thus, have higher gross margin per hectare. Tree/crop interface effect indicated that crop yield does not hampered when trees are prunned frequently at low height (approx. 1.5 meter) while the yield is hamper with unpruned trees. Linear programming model shows that growing kidney bean in upland and soybean in lowland is profitable. The land constraint is common in both villages. However, shadow price of winterland is higher than summarland in the study villages. The growing of fodder trees on farm has direct impact on the condition of forest near by village. The forestin the near by project village is in better condition than that of forest near by control village. It is because of the fact that control village has to depend on forest fodder (42%) as compared to 10 % of project village. A dominant proportion (38%) of fodder in project village is supplied through farm fodder tree source. There is not much variation in feeding practice of animal. Small difference has been observed in grazing pattern where 40 percent of households in the control village practice grazing of livestock in the forest against 33 percent of the households of project village. The evaluation of NAF extension process shows that the promotion of agroforestry program through home nursery approach is more effective than does through community nursery approach where farmer group plays a key role in the success of the program. The study shows that the farmers who followed home nursery approach at Kundar are found selfsufficient in fodder production.
Thesis (M.Sc.) - Asian Institute of Technology, 1994
A Thesis Submitted in Partial Fulfilment of the Requirements for the Degree of Master of Science.
Keywords: Agroforestry -- Nepal